Optimizing Public Service Through E-Gov Services (The Case of Public Service in South Jakarta Municipality) - Florentina Ratih Wulandari; 2Yuli Tirtariandi El Anshori (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2012)
The development of information technology and public administration paradigms that emphasize services for the benefit of society has affected the strategic efforts of e-Gov in Indonesia. For that, there is a need to create qualified, competitive, effective and efficient of the public services. Indonesia’s E-Gov Policy has been applying principles of good governance and information technology to serve and interact with the community. Some local governments, including South Jakarta Municipality has been implementing e-Gov to optimize public service. e-Gov in South Jakarta Municipality is reflected on the implementation of a management information technology to improve services to the community by creating a web site, namely http://selatan.jakarta.go.id/. The information presented in South Jakarta Municipality website includes tourism, local regulations, and other information of Municipality of South Jakarta. This article is the result of field research entitled “The Role of Information Systems Management in the Creation of Competitive Advantage and Quality Improvement Services Public Information” in South Jakarta Municipality. The result shows that public service in website South Jakarta Municipal Government used to support the plan of development of e-Gov is still in the stage information dissemination, not two way interaction. Public service website run by South Jakarta Municipality is planned to integrate services on the process to obtain civic identity cards, urban planning permits, tourism, population, building permits et cetera. e-Gov applications using information technology in the office of South Jakarta Municipality still has many obstacles, i.e human resources, budget used and infrastructure.